The Shortened Dental Arch Concept: Awareness, Knowledge, and Practice of Dentists in Dubai and the Northern Emirates, United Arab Emirates - Haleimah AlHmoudi; Amar H. Khamis; Haitham Elbishari; Fatemeh Amir-Rad (International Journal of Dentistry)
Background and objectives. The shortened dental arch (SDA) is a dentition of no more than twenty teeth with an intact anterior region but a reduced number of occluding pairs of posterior teeth. The SDA concept is a valid treatment option in cases in which anteriors and premolars can provide adequate aesthetics, function, and occlusal stability. This study investigated dentists’ awareness and opinion of the shortened dental arch (SDA) concept among UAE dentists and its application in their practice. Methods. This is a cross-sectional study utilizing an online questionnaire anonymously to investigate the awareness and views of dentists about SDA. The questionnaire was sent to all 901 dentists registered with the Emirates Medical Association (EMA). The questionnaire consists of 17 questions, which comprise demographics, awareness, and application in dental practice, preferred treatment modality, and risks and benefits associated with SDA. The data were analyzed using SPSS Statistics. Results. The response rate reported was 40.3%. Two-thirds of the respondents (65.8%) were aware of the SDA concept; however, it was not usually applied in clinical practice (n = 196, 54.7%). Specialists were more aware of the concept (p≤0.001) and applied it more frequently in their clinical practice (p=0.041) than general dental practitioners (GDPs). Respondents agreed that SDA was associated with the risks of teeth migration (n = 211, 59.9%), tooth wear (n = 196, 55.8%), and/or temporomandibular disorder (TMD) (n = 163, 45.3%). The implant was the treatment of choice for many of the participants (n = 169, 46.6%) to replace missing molars, followed by the acrylic removal partial denture (RPD) (n = 129, 35.5%). Conclusions. Most dentists who responded to this survey were aware of the SDA concept and had a positive attitude about it. However, they did not apply it frequently in their clinical practice.